Good governance and corruption in local governments: The role of internal control and audit - Shidqi, Farhan; Arfiansyah, Zef (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
This study investigates the effects of internal controls, internal audit functions, audit opinions, and capital expenditures on corruption in local governments. Using a panel dataset of 519 local governments over the 2018–2022 period (2,595 observations), the study employs a fixed-effect regression with robust standard errors. The results indicate that internal controls and a more mature internal audit function significantly reduce corruption, while capital expenditure is positively associated with corruption levels. By contrast, audit opinion and lower-level audit capabilities have no significant impact. These findings highlight the importance of strengthening internal governance mechanisms to reduce corruption risk in public sector entities. Policy implications are directed toward local government leaders, auditors, and regulators to enhance internal oversight, professional competence, and qualitative judgment in financial reporting.